Respons terhadap Komunitas AnieSpace sebagai Bentuk Ruang Publik Baru - Cesta Izzati Ukarana; Muhamad Suharbillah; Al Fuji Istiqomah; Pia Khoirotun Nisa (MUKASI: Jurnal Ilmu Komunikasi, 2024)
In the era of digital transformation, the concept of public space has experienced a significant shift. Traditional public spaces such as parks and squares are no longer the only platform for social interaction. Twitter or what has now changed its name to X is a new public space, which shows the characteristics of what Habermas said is a space that supports and allows political criticism to be discussed. AnieSpace is a community on the X platform which has emerged as a new public space in the digital realm. The aim of this research is to analyze the AnieSpace community as a new public space and determine the response to the AnieSpace community as a new form of public space. Researchers used qualitative literature study methods and also interview methods. The results of the research show that the AnieSpace community is an example of a public space that meets the criteria. The response to the new public space AnieSpace was very positive, which was marked by the increase in the electability of candidate pair 01. Communication via AnieSpace was greeted with enthusiasm by the public, as evidenced by the high number of listeners in the initial discussion.